Surgical Management of Recurrent Tracheocarotid Fistula following Endovascular Stent Placement - Jeffrey T. Steitz; Zachary J. Cappello; Ziad Katrib; Paul A. Tennant (Case Reports in Otolaryngology)
We report the case of a 25-year-old woman who developed a tracheocarotid fistula secondary to an infected endovascular stent placed in the right carotid artery after the patient experienced hemorrhage on her first tracheostomy change. The patient originally had the tracheostomy placed at an outside hospital in September 2014, due to prolonged intubation after a motor vehicle accident. The patient presented to the otolaryngology service with an acute tracheal hemorrhage. This necessitated a neck exploration, median sternotomy, right carotid stent removal with subclavian to carotid bypass, and sternocleidomastoid flap reconstruction. This paper addresses the epidemiology and anatomy of a tracheocarotid fistula and discusses methods to treat such a complication.